Ag-Se phase diagram calculation associating ab−initio molecular dynamics simulation. (December 2018) - Rajkumar, V.B.; Chen, Sinn-wen
Abstract: This study carries out thermodynamic modeling of the Ag-Se system using the calphad approach. The Ag-Se phase diagram is deduced from the available constitutional and thermochemical information. Thermodynamic information pertaining to liquid is scarce because of the experimental difficulty. Hence the enthalpy of mixing for liquid at 1273 K is generated in this study using ab − initio molecular dynamics (AIMD) simulation. The solution and the associate model describe the Gibbs energy of the liquid phase. The presence of Ag 2 Se associates in the liquid demands an associate model whereas the solution model is for the compatibility of the thermodynamic databases. The Wagner-Schottky model describes the Gibbs energy of the intermetallic phases that has ample of constitutional and thermochemical information in the literature. The constitutional and thermochemical properties that are calculated are compared with those in literature.